Bibliographic analysis: Research prospects for work-life balance of women workers in engineering - Zetli, Sri; Susanti, Lusi; Jumeno, Desto (Universitas Sultan Ageng Tirtayasa, 2024)
Work-life balance is a significant issue today, especially for women workers, who often experience role conflict. Besides their professional roles, women also have responsibilities at home, making balancing work and life outside the workplace one of their primary challenges. This article aims to analyze scientific publications on work-life balance among female workers using bibliometric analysis to identify research opportunities in the field of engineering. The Scopus database was utilized for data mining, and data analysis was conducted using VOSviewer. A total of 123 documents were identified from the 2019–2024 period, with South Korea leading in publications (15 documents and 63 citations), followed by the United States, which had fewer publications (14 documents) but the highest number of citations (240 citations). The research subject areas were predominantly Medicine (27.8%), with only 4.7% focusing on Engineering. The majority of research subjects were healthcare workers (33%), while only 5% specialized in the industrial sector. The International Journal of Environmental Research and Public Health was the most frequently referenced source. Commonly discussed impacts of work-life balance influenced by gender include mental health, job satisfaction, and burnout. However, no studies specifically focus on female workers in the manufacturing industry to examine the effects of work shifts on work-life balance and their implications for occupational health and safety, work accidents, and musculoskeletal pain. Future research should address this gap by applying engineering studies to explore these challenges.